Sp8 expression in putative neural progenitor cells in guinea pig and human cerebrum. Issue 9 (30th November 2015) - Zhang, Xue‐Mei; Cai, Yan; Wang, Fang; Wu, Jun; Mo, Lin; Zhang, Feng; Patrylo, Peter R.; Pan, Aihua; Ma, Chao; Fu, Jin; Yan, Xiao‐Xin
ABSTRACT: Neural stem/progenitor cells have been characterized at neurogenic sites in adult mammalian brain with various molecular markers. Here it has been demonstrated that Sp8, a transcription factor typically expressed among mature GABAergic interneurons, also labels putative neural precursors in adult guinea pig and human cerebrum. In guinea pigs, Sp8 immunoreactive (Sp8+) cells were localized largely in the superficial layers of the cortex including layer I, as well as the subventricular zone (SVZ) and subgranular zone (SGZ). Sp8+ cells at the SGZ showed little colocalization with mature and immature neuronal markers, but co‐expressed neural stem cell markers including Sox2. Some layer I Sp8+ cells also co‐expressed Sox2. The amount of Sp8+ cells in the dentate gyrus was maintained 2 weeks after X‐ray irradiation, while that of doublecortin (DCX+) cells was greatly reduced. Mild ischemic insult caused a transient increase of Sp8+ cells in the SGZ and layer I, with the subgranular Sp8+ cells exhibited an increased colabeling for the mitotic marker Ki67 and pulse‐chased bromodeoxyuridine (BrdU). Sp8+ cells in the dentate gyrus showed an age‐related decline in guinea pigs, in parallel with the loss of DCX+ cells in the same region. In adult humans, Sp8+ cells exhibited comparable morphological features as seen in guinea pigs, with those at the SGZ and some in cortical layer I co‐expressed Sox2. Together, these results suggested that Sp8 may label putative neural progenitors in guinea pig and human cerebrum, with the labeled cells in the SGZ appeared largely not mitotically active under normal conditions. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 76: 939–955, 2016